Faktor-Faktor Yang Memengaruhi Persepsi Karyawan Dalam Pencegahan Fraud (Studi Empiris Pada PT. BPR BKK Kabupaten Pekalongan (Perseroda)) - Norma Yustia Hanurani; Jaeni (Universitas Sains dan Teknologi Komputer, 2022)
This study aims to determine the effect of employee perceptions of the culture of honesty, whistleblowing system and internal control system on fraud prevention. This study is a quantitative study using primary data obtained from questionnaires and measured using a Likert scale. The population in this study were all employees of PT BPR BKK Pekalongan Regency (Perseroda). The sampling technique used purposive sampling with sample criteria, in order to obtain a sample of 104 people. The data analysis technique used multiple linear regression analysis using the SPSS version 25 program. The results showed that the culture of honesty and the internal control system had a positive and significant effect on fraud prevention. Meanwhile, the whistleblowing system has no effect on fraud prevention.